Modeling life : art models speak about nudity, sexuality, and the creative process - Phillips, Sarah R., 1963- (State University of New York Press, 2006)
"Making use of extensive interviews with both male and female models and quoting them frequently, Sarah R. Phillips gives a voice of life models. She explores the meaning that life models give to themselves and to their work and seeks to understand the lived experience of life models as they practice their profession. Throughout history, people have romanticized life models in an aura of bohemian eroticism, or condemned them as strippers or sex workers. Modeling Life reveals how life models get into the business, managing sexuality in the studio, what is means to be a "muse," and why their work is important."--Jacket